La gamificación en la atención de los estudiantes de segundo año de Educación Básica - Panchana Espinoza, Nicole Patricia (2024)
The present research work addresses the current problem in the school context characterized by the lack of knowledge and underuse of pedagogical tools that strengthen the fundamental cognitive ability in children of childhood age, attention. Given this reality, the urgency of implementing innovative pedagogical techniques, such as gamification, is highlighted to address this lack and enrich the educational experience. And, on the other hand, contribute to the eradication of ignorance of this within the knowledge acquisition processes. The main objective of the research was to analyze the influence of gamification on the attention of the students of the Unidad Educativa “Indoalemán”. Adopting a descriptive approach with both qualitative and quantitative methodology, instruments such as an interview, observation sheets and educational tests were used to collect data. Through a rigorous analysis, it is determined that the results obtained conclusively revealed the positive influence of gamification on pedagogical processes, evidencing its ability to significantly improve student attention. These instruments show a favorable perception towards gamification, highlighting its ability to maintain interest and improve participation. Gamified activities generated greater attention and engagement than traditional ones.............